EFEKTIVITAS EKSTRAK JAHE MERAH (Zingiber officinale Rosc.) SEBAGAI BIOPESTISIDA TERHADAP HAMA PADA TANAMAN BAYAM (Amaranthus sp.) SEBAGAI RANCANGAN BOOKLET MATERI BIOTEKNOLOGI SMA - Sri Wilda Yanti; Imam Mahadi; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Biopesticide is the result of extracting certain parts of plants from leaves, fruit, seeds or roots which have compounds that are toxic to pests or organisms that interfere the plants. The basic ingredient used as a biopesticide in this research is red ginger (Zingiber officinale Rosc.). This study aims to determine the effectiveness of red ginger (Zingiber officinale Rosc.) extract as a biopesticide to pests on spinach plants (Amarantus sp.). This study used a quantitative approach and the type of research was completely randomized design (RAL). The results showed that the effective concentration in the use of biopesticides was at a concentration of 100% with the level of damage being in the mild category with a damage value of 11.66%. The results of the red ginger extract research can be used as a source of learning and the resulting learning media is in the form of a booklet.Key Words: effectiveness of biopesticides, red ginger, spinach plants